Estudio de prefactibilidad para la instalación de una planta productora de salsa picante con ají charapita (capsicum frutescens) para el mercado local (Lima) - Quispe Velásquez, Fernando (2015)
In this investigation, we evaluate the technical and economic feasibility for the installation of a plant that produces spicy sauce with Charapita capsicum, in order to comply with the market demand with this new product; which, will be at an affordable price and, of course, will have a pleasant and delicious taste, perfect to eat with any kind of foods.